Penerapan Model Problem-Based Learning berbantuan GeoGebra untuk Meningkatkan Kemampuan Literasi Matematis Siswa SMA - Nida Amelya Al Fitriani; Darta Darta; Thesa Kandaga (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2023)
Mathematical literacy ability is an important ability possessed by students. However in reality mathematical literacy ability is still low. One of the learning models that can help to improve mathematical literacy ability is the PBL model with GeoGebra. This study aims to find out the increase in mathematical literacy ability of students who obtain PBL model with GeoGebra is higher than those who obtain ordinary learning model. The method in this study is quasi-experimental with nonequivalent control group desain. The population of this study was XI students SMA Pasundan 2 Bandung for academic year 2022/2023. The research instrument used was a description test of the ability to mathematical literacy. Processing and analyzingd data on the difference between the two averages using thr Mann-Whitney U test. Based on the results of data analysis, it was concluded that the increase in mathematical literacy ability of students who obtain PBL model with GeoGebra is higher than those who obtain ordinary learning model.